PENGARUH DEBT TO ASSET (DAR), RETURN ON ASSET (ROA), DAN CURRENT RATION (CR) TERHADAP HARGA SAHAM PADA PERUSAHAAN SUBSEKTOR TOURISM, RESTAURANT AND HOTEL YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2018-2022 - Priska Br Tarigan; Herlina Novita; Widia Br Barus (Institut Teknologi dan Bisnis Kristen Bukit Pengharapan, 2024)
This research aims to analyze and test the influence of Debt To Asset (Dar), Return On Asset (Roa), and Current Ration l(Cr) lon lshare lprices lin ltourism, lrestaurant land lhotel lsubsector lcompanies llisted lon lthe lIndonesian lStock lExchange lin 2018-2022. The independent variables in this research are Debt To Asset (Dar), Return On Assets (Roa), land lCurrent lRation l(Cr). lThe ldependent lvariable lis lshare lprice. lThe lpopulation lin lthis lstudy lis lthe ltourism, lrestaurant land lhotel lsubsector lcompanies llisted lon lthe lIndonesian lStock lExchange lin l2018-2022, ltotaling l48 lcompanies land lthe lsample lis l2 lcompanies. ltesting land ldata lanalysis lusing lE lViews l12 lsoftware. lUsing lthe lmultiple llinear lregression lanalysis lmethod, lthe ltest lresults lshow lthat lpartial ltesting lof lDAR lhas la lpositive land lsignificant leffect lon lstock lprices, lROA lhas la lnegative land linsignificant leffect lon lstock lprices, lCR lhas la lpositive land linsignificant leffect lon lprices. lshare. lSimultaneous ltesting lof lDAR, lROA, land lCR linfluences lstock lprices.